Water Footprint of Cereals and Vegetables for the Beijing Market. (19th July 2013) - Huang, Jing; Ridoutt, Bradley G.; Zhang, Hailin; Xu, Changchun; Chen, Fu
Summary Beijing is situated in water‐scarce northern China, where there is a history of policies aimed at constraining local agricultural water use to meet the increasing urban water demand. This has led to a change in local crop production and subsequent effects in terms of the importation of cereals and vegetables grown in other parts of China. The dilemma is that local policies designed to improve Beijing's water resources situation may have the unintended consequence of increasing water stress in other regions. In this article, life cycle assessment approaches were used to model both consumptive and degradative water use for the major cereals and vegetables consumed in Beijing, enabling comparison of local and imported supplies. In the Beijing region, cropping cereals rather than intensive vegetables in greenhouses could reduce local blue water consumption by 7, 216 cubic meters per hectare per year (m3 ha−1 yr−1) and nitrogen pollution by 45 kg ha−1 yr−1. However, depending on how the local food shortfall is balanced by imported food, shifts in cropping pattern in Beijing have the potential to cause either an improvement or exacerbation of the nationwide water stress situation (e.g., −42% to 4% for water scarcity footprint). As such, local policy making regarding agricultural land and water use needs to consider the wider food production context. This situation in Beijing is likely to be representative of the challenge facing many of the world's large and mega‐sized cities, where a sustainable means of increasing food supply must be found.